Provision of Global Economic and Energy Security in the Context of the Development of the Arctic Resource Base by Industrialized Countries - Dudin, Mihail Nikolaevich; Lyasnikov, Nikolaj Vasil'evich; Sekerin, Vladimir Dmitriyevich; Gorohova, Anna Evgen'evna; Bank, Sergey Valeryevich (International Journal of Economics and Financial Issues, 2015)
Some issues related to the problems of development of the Arctic and subarctic areas, which according to various expert estimates contain between 15% and 25% of the world reserves of primary energy resources, are presented and disclosed in this article. The purpose of this article is to develop a system of global economic and energy security provision in the context of advanced deposits developments in the Arctic. The goals set were consistently achieved, in particular: the general trends of the energy development of civilization were examined, the legal issues concerning the status of the subarctic and Arctic regions were considered, and the basic global trends of world energy development and the system of global energy security provision were defined. The following fundamental findings were obtained: Firstly, the subarctic and Arctic areas represent world heritage, so the development of deposits therein should be in the interests of the world community on a non-discriminatory basis. Secondly, civilization's future energy supplies will be based on the harmony of traditional and renewable energy sources, which determines the need to rationalize the consumption of energy resources at present. Thirdly, the environmental issues of prospective development of the Arctic and subarctic areas are sufficiently acute and debatable that non-aggressive technologies of primary energy resource extraction from the Arctic fields should be used. Significant reserves of hydrocarbon resources in the Arctic shelf allow estimation of a significant global rental potential, despite the territorial remoteness and difficult climatic conditions that greatly increase the cost of development in these areas. Therefore, the planning and management of the Arctic and subarctic areas should be considered as a strategic reserve of sustainable global socio-economic development. Keywords: Energy Security; arctic; industrialized countries; economic security; resources JEL Classifications: Q41; Q47; Q56